The Ashgate research companion to religion and conflict resolution - Marsden, Lee (Religion and international security, 2012)
This Companion provides a comprehensive overview of the latest research in religion and conflict resolution and brings together leading scholars in the field who examine the contribution religious actors have made and are making towards peace and conflict resolution. The twenty-three essays are grouped in to five thematic sections: religious traditions and conflict; key debates on religious conflict resolution; religion, international relations and security; religion and conflict resolution; the peacemakers. The Companion is aimed at academics and practitioners interested in conflict resolution, international security, and religion and international relations.